Innovative Technology Based Interventions for Psychological Treatment of Common Mental Disorders - Donker, Tara; Kleiboer, Annet (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Mental health disorders such as depression, anxiety, and other stress-related disorders are highly prevalent and even increasing in incidence globally, while access to evidence-based therapy remains limited. Worryingly, health care budgets are further restrained, thus limiting the availability of mental health care even more. Innovative technologies aiming to increase scalability, accessibility, and cost-efficiency of evidence-based mental health treatment, or target hard-to-reach populations, show promising solutions toward preventing or treating such disorders. However, despite considerable progress in this area, more research into innovative technologies and its implementation in mental health care is needed to treat people with-or prevent-mental health disorders. The present Special Issue aims to provide an overview of the latest innovative technological advances in the screening and treatment of mental health as well as their implications for mental health care. Both original research and review papers will inform researchers and clinicians with recent knowledge on innovative technology in the area of psychological treatments of common mental disorders and e-mental health.